2017
DOI: 10.1016/j.apor.2017.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of a wave energy spectrum from encounter to absolute domain when observing from an advancing ship

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 3 publications
1
33
0
Order By: Relevance
“…Thus, the whole set of estimated encounter-wave spectra are shown in Figures 5 and 6. Obviously, the corresponding wave spectra -in absolute domain -seen previously in Figures 2 and 3 have been obtained by transformation of the encounter-wave spectra by applying the particular transformation algorithm [15], specifically developed to transform a spectrum from encounter to absolute domain, but not the "other way". The reason to transform to absolute domain is that the estimated encountered wave spectrum cannot be used to deduce any consequence of speed or heading changes of the vessel, which is the objective of decision support systems and also in more general response calculations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the whole set of estimated encounter-wave spectra are shown in Figures 5 and 6. Obviously, the corresponding wave spectra -in absolute domain -seen previously in Figures 2 and 3 have been obtained by transformation of the encounter-wave spectra by applying the particular transformation algorithm [15], specifically developed to transform a spectrum from encounter to absolute domain, but not the "other way". The reason to transform to absolute domain is that the estimated encountered wave spectrum cannot be used to deduce any consequence of speed or heading changes of the vessel, which is the objective of decision support systems and also in more general response calculations.…”
Section: Resultsmentioning
confidence: 99%
“…[12]- [14], but giving no solution on how to deal with the problem in practice, when a wave spectrum (or a response spectrum) shall be transformed from encounter frequencydomain to absolute frequency-domain; a process that theoretically cannot be uniquely solved as it relates one single encounter frequency to three absolute frequencies in following seas. On the other hand, an interrelated study by Nielsen [15] outlines explicitly an elaborate and practical solution strategy for this problem. The details of the particular work will not be covered herein, but later additional referencing will be made to the study [15].…”
Section: Methodology and Estimation Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Nielsen et al suggested a new method in 2015 which is to make the fitting of the measured response and the corresponding theoretically calculated one directly in the time domain [15,16]. Subsequently, Nielsen has proposed a practical approach which is a transformation from encounter to an absolute domain of wave spectral densities, and it is considered that this method is satisfactory through numerical simulation and experimental verification [17]. Brodtkorb et al developed a simple method to solve the wave spectrum by using the iteration method.…”
Section: Introductionmentioning
confidence: 99%